Design - culture - identity : the Wolfsonian collection : exploring the period 1875-1945 - Hoffmann, Joel M.; Bowlt, John E.; Kinchin, Juliet (Miami Beach : The Wolfsonian-Florida International University, 2002)
Contents:##- Defining the Wolfsonian Collection through objects, presentations, and perceptions / Joel M. Hoffman ##- Stalin as Isis and Ra: socialist realism and the art of design / John E. Bowlt ##- Modernity and tradition in Hungarian furniture, 1900-1938: three generations / Juliet Kinchin ##- W. A. S. Benson, machinery, and the arts and crafts movement in Britain / Alan Crawford ##- Feast of Dutch diversity: Nieuwe Kunst book design / Alston W. Purvis ##- Mobilizing the nation: Italian propaganda in the Great War / Thomas Row ##- The Tripoli Trade Fair and the representation of Italy's African colonies / Brian L. McLaren ##- From World War I to the Popular Front: the art and activism of Hugo Gellert / James Wechsler ##- Looking at labor: images of work in 1930s American art / Erika Doss ##- "Painting Section" in black and white: Ethel Magafan's Cotton Pickers / Susan Valdés-Dapena.
Florida International University
boek